2014
DOI: 10.5812/ircmj.21110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Discussion on the Quality of Life and HbA1c Levels of Adolescents With Diabetes

Abstract: Background:Diabetes is a metabolic syndrome and the most common endocrine disorder in childhood and adolescence. Diabetes occurs at any age but the highest outbreak is during ten to 15 years of age and 75% of the cases are diagnosed at the age 18.Objectives:This study aimed to investigate the effect of a group discussion on the quality of life (QOL) and glycosylated hemoglobin A (HbA1c) levels of adolescents with diabetes.Patients and Methods:This quasi-experimental study was performed on 56 adolescents with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Afshar et al also found that sessions with group discussions could lead to improvement of quality of life for patients with diabetes. Along with other methods, e-learning has resulted major changes in education (20). This exclusive method enables learners learn anything, anywhere (21).…”
Section: Introductionmentioning
confidence: 99%
“…Afshar et al also found that sessions with group discussions could lead to improvement of quality of life for patients with diabetes. Along with other methods, e-learning has resulted major changes in education (20). This exclusive method enables learners learn anything, anywhere (21).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study women's blood sugar scores were related to outcome expectations, behavioral intent, and maintenance self-e cacy. Expecting a good outcome seems to have a better commitment [25] . People need to know how to adjust their behavior by understanding the possibilities between their actions and the consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the complexity of health and treatment issues in the contemporary world, responsibility and participation in self-care and treatment is not only the awareness of the nature of the disease; it is also necessary to create motivation and positive attitudes with social support for hemophilia patients (17).…”
Section: Hemophiliamentioning
confidence: 99%